A functional type II-A CRISPR–Cas system from Listeria enables efficient genome editing of large non-integrating bacteriophage. Issue 13 (22nd June 2018) - Hupfeld, Mario; Trasanidou, Despoina; Ramazzini, Livia; Klumpp, Jochen; Loessner, Martin J; Kilcher, Samuel
Abstract: CRISPR–Cas systems provide bacteria with adaptive immunity against invading DNA elements including bacteriophages and plasmids. While CRISPR technology has revolutionized eukaryotic genome engineering, its application to prokaryotes and their viruses remains less well established. Here we report the first functional CRISPR–Cas system from the genus Listeria  and demonstrate its native role in phage defense. LivCRISPR-1 is a type II-A system from the genome of L. ivanovii subspecies londoniensis that uses a small, 1078 amino acid Cas9 variant and a unique NNACAC protospacer adjacent motif. We transferred LivCRISPR-1 cas9 and trans-activating crRNA into Listeria monocytogenes . Along with crRNA encoding plasmids, this programmable interference system enables efficient cleavage of bacterial DNA and incoming phage genomes. We used LivCRISPR-1 to develop an effective engineering platform for large, non-integrating Listeria phages based on allelic replacement and CRISPR-Cas-mediated counterselection. The broad host-range Listeria phage A511 was engineered to encode and express lysostaphin, a cell wall hydrolase that specifically targets Staphylococcus peptidoglycan. In bacterial co-culture, the armed phages not only killed Listeria hosts but also lysed Staphylococcus cells by enzymatic collateral damage. Simultaneous killing of unrelated bacteria by a single phage demonstrates the potential of CRISPR–Cas-assisted phage engineering, beyond single pathogen control.